DIGITAL ASSET INVESTMENT POLEMIC IN INDONESIA FROM AN ISLAMIC PERSPECTIVE - Rico Nur Ilham; Arliansyah; Reza Juanda; Irada Sinta; Muhammad Multazam; Frengki Putra Ramansyah (CV. Radja Publika, 2024)
Cryptocurrency is one of the investment commodities that can generate returns and already has a permit to be traded in exchange trading through the Indonesian Commodity Futures Trading Supervisory Agency (BAPEPTI). Digital crypto assets traded in Indonesia are quite a lot through the Indodax trading company. The purpose of this study is focused on formulating a risk management process in investing in digital cryptocurrency assets. In addition, the results of this study will produce policy recommendations known as LCTR or